Nationwide projections of ischemic stroke with large vessel occlusion of the anterior circulation by 2050: Dijon Stroke Registry - Duloquin, Gauthier; Béjot, Yannick (Frontiers in Public Health, 2023)
Introduction: Data on the epidemiology of ischemic stroke (IS) with large vessel occlusion (LVO) are scarce although there is a need to better assess future demands for dedicated facilities in an aging population. This study aimed to estimate the number of expected cases of IS with LVO of the anterior circulation in the French population by 2050. Methods: IS were retrieved from the population-based registry of Dijon, France (2013-2017). Patients with LVO were identified and age- and sex-standardized incidence rates were calculated to estimate the number of expected cases in the whole French population by 2050 according three scenarios: stable incidence; a decrease in incidence rates of 0.5%/year in people >65 years old; a decrease in incidence rates of 0.5%/year in overall population. Results: 1067 cases of IS with LVO were recorded in Dijon over the study period, corresponding to crude incidence rate of 22/100,000/year (95% CI: 18-25). By 2050, the number of cases is expected to increase by 51% to 81% according to the various scenarios, to reach between 22,457 cases (95% CI: 10,839 – 43,639) and 26,763 cases (95% CI: 12,918 – 52,008) annually. This increase will be mainly driven by patients >80 years old, with a rise of cases between +103% and +42% in this age group. The proportion of patients >80 years old among overall IS with LVO will increase from 43% to 57% approximately. Conclusion: The expected massive increase in IS with LVO highlights the need for a rapid action to cover stroke care requirements.